On Grand-Mentors and Great-Grand-Mentors: Reflflecting on Graduate Program Support for a Multigenerational Mentorship Model - Mackenzie DM Whipps; Julia Honoroff; Hope Salvador; Hirokazu Yoshikawa; Edward Seidman (New Prairie Press, 2022)
Doctoral programs often reflect a formal mentoring project wherein an advisor closely guides a junior scholar through degree completion. But the primary mentor-mentee relationship is only one of many relationships that blossoms during this time. 'Mosaic' mentorship models are becoming more common, leading to better outcomes for junior scholars. In this commentary, we reflect on one type of mosaic mentorship model wherein multiple 'generations' mentor more junior scholars (and mentor those who are doing the mentoring, too). The authors are five links in this continuing mentorship chain. Together we reflect on what made this style of mentorship a unique and positive experience, and how graduate programs can support their students by encouraging this model.